2023
DOI: 10.3390/genes14030661
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Genes Associated with Female Flower Development of Phellodendron amurense Rupr. Using a Transcriptomics Approach

Abstract: Phellodendron amurense Rupr., a species of Rutaceae, is a nationally protected and valuable medicinal plant. It is generally considered to be dioecious. With the discovery of monoecious P. amurense, the phenomenon that its sex development is regulated by epigenetics has been revealed, but the way epigenetics affects the sex differentiation of P. amurense is still unclear. In this study, we investigated the effect of DNA methylation on the sexual development of P. amurense. The young inflorescences of male plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 225 publications
0
0
0
Order By: Relevance
“…MCM6 was associated with gynoecium sex expression in different species and was involved in sexual differentiation (Vinay et al 2023 ). Recently, it was found that in A. thaliana, CDT1A is expressed in pollen sperm cells before fertilization (Voichek et al 2023 ; He et al 2023 ). Interestingly, mutation of CDT1A produces genotypes that, after two rounds of mitosis, produce abnormal embryo sacs with only four nuclei, which is exactly what happens in the normal E. curvula apomictic embryo sac development (Crane 2001 ; Domenichini et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…MCM6 was associated with gynoecium sex expression in different species and was involved in sexual differentiation (Vinay et al 2023 ). Recently, it was found that in A. thaliana, CDT1A is expressed in pollen sperm cells before fertilization (Voichek et al 2023 ; He et al 2023 ). Interestingly, mutation of CDT1A produces genotypes that, after two rounds of mitosis, produce abnormal embryo sacs with only four nuclei, which is exactly what happens in the normal E. curvula apomictic embryo sac development (Crane 2001 ; Domenichini et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%